2017
DOI: 10.1016/j.jsat.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Treatment seeking as a mechanism of change in a randomized controlled trial of a mobile health intervention to support recovery from alcohol use disorders

Abstract: Background We estimated the efficacy of the Addiction-Comprehensive Health Enhancement Support System (A-CHESS) in increasing the use of services for addiction and examined the extent to which this use of services mediated the effects of A-CHESS on risky drinking days and abstinence from drinking. Methods We conducted secondary data analyses of the A-CHESS randomized controlled trial. Recruitment occurred in five residential treatment programs operated by two addiction treatment organizations. Participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 35 publications
0
59
0
3
Order By: Relevance
“…It should be noted that the positive results in this paper could have simply reflected self-selection, with more motivated participants both accessing A-CHESS more frequently and having better outcomes. Finally, a fourth study found that the effects of A-CHESS on the risky drinking days outcome was mediated by participation in outpatient SUD treatment [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the positive results in this paper could have simply reflected self-selection, with more motivated participants both accessing A-CHESS more frequently and having better outcomes. Finally, a fourth study found that the effects of A-CHESS on the risky drinking days outcome was mediated by participation in outpatient SUD treatment [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Online support has been used to complement face to face treatment following residential programs in the US. Training was provided to patients before they left the facility and this additional online support meant they were more likely to seek additional face to face treatment once they had been discharged (Glass et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a forth study found that the effects of A-CHESS on the risky drinking days outcome was mediated by participation in outpatient SUD treatment (Glass et al, 2017).…”
Section: Intervention Effects On Substance Use Outcomesmentioning
confidence: 89%
“…Four of the papers on complex interventions also reported some information on effects on other outcomes than substance use. Gustafson [64] found that A-CHESS had no impact on negative consequences of drinking, Glass et al (2017) reported that A-CHESS increased participation in outpatient treatment following rehabilitation, Schaub [83] found that Can Reduce did not affect mental health measures, and Tait [84] found that the intervention they studied made no difference on psychological distress. On the other hand, Tait found that the intervention led to a significant reduction in days of general impairment.…”
Section: Intervention Effects On Other Outcomesmentioning
confidence: 99%